Pengaruh Teknik Pernapasan Buteyko Terhadap Frekuensi Kekambuhan Asma Bronkial di Wilayah Kerja UPTD Puskesmas Lingkar Timur Kota Bengkulu Tahun 2025 - Nurazizah Salsabillah; Danur Azissah RS; Kartika Murya Ningrum (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Bronchial asthma is a chronic respiratory disease characterized by shortness of breath, coughing, and wheezing that can recur. The prevalence of asthma in Bengkulu Province reaches 1.4% (SKI 2023), and Lingkar Timur Community Health Center is among the areas with the highest number of sufferers. The Buteyko breathing technique is a non-pharmacological therapy aimed at improving breathing patterns. This study aimed to determine the effect of the Buteyko technique on the frequency of bronchial asthma relapses. The study used a quasi-experimental design with a one-group pre-test post-test design. The sample consisted of 18 respondents selected based on inclusion and exclusion criteria. Data on the frequency of relapses were collected before and after the Buteyko technique intervention and analyzed using a paired t-test. The results showed a significant reduction in the frequency of asthma relapses after Buteyko breathing technique implementation with a p-value <0.05, indicating that this technique is effective in reducing bronchial asthma relapses. Healthcare professionals are advised to educate asthma patients about the Buteyko technique as a supportive therapy. Community health centers can integrate these exercises to help control symptoms and improve patients' quality of life.